New data from Oman indicate benthic high biomass productivity coupled with low taxonomic diversity in the aftermath of the Permian–Triassic Boundary mass extinction. (31st July 2018) - Brosse, Morgane; Bucher, Hugo; Baud, Aymon; Frisk, Åsa M.; Goudemand, Nicolas; Hagdorn, Hans; Nützel, Alexander; Ware, David; Hautmann, Michael
Abstract : A new Early Triassic marine fauna is described from an exotic block (olistolith) from the Ad Daffah conglomerate in eastern Oman (Batain), which provides new insights into the ecology and diversity during the early aftermath of the Permian–Triassic Boundary mass extinction. Based on conodont quantitative biochronology, we assign a middle Griesbachian age to the upper part of this boulder. It was derived from an offshore seamount and yielded both nektonic and benthic faunas, including conodonts, ammonoids, gastropods and crinoid ossicles in mass abundance. This demonstrates that despite the stratigraphically near extinction at the Permian–Triassic Boundary, Crinoidea produced enough biomass to form crinoidal limestone as early as middle Griesbachian time. Baudicrinus, previously placed in Dadocrinidae, is now placed in Holocrinidae; therefore, Dadocrinidae are absent in the Early Triassic, and Holocrinidae remains the most basal crown‐group articulates, originating during the middle Griesbachian in the Tethyan Realm. Abundant gastropods assigned to Naticopsis reached a shell size larger than 20 mm and provide another example against any generalized Lilliput effect during the Griesbachian. Whereas the benthic biomass was as high as to allow the resumption of small carbonate factories, the taxonomic diversity of the benthos remained low compared to post‐Early Triassic times. This slow benthic taxonomic recovery is here attributed to low competition within impoverished post‐extinction faunas.